Perfectionism and fear of failure, according to sporting experience. A referee handball study - Gómez-López, M.; Manzano-Sánchez, D.; Borrego, C. C.; González-Hernández, J. (Frontiers in Psychology, 2025)
Introduction: Fear of failure is a motive to avoid failure in evaluative situations based on anticipatory shame upon failure. Perfectionism is a personality disposition characterized by striving for flawlessness and setting exceedingly high standards of performance accompanied by overly critical evaluations of one`s behavior. The goal of the study was to describe the effects of previous sports experiences that handball referees had, related to perfectionism and fear of making mistakes.